The Urgency of Establishing a Social Welfare Center (Puskesos) in Cirebon City - Faoziyah, Sitti (GoAcademica Research & Publishing, 2023)
This research discusses the urgency of establishing a Social Welfare Center (Puskesos) in Cirebon City as a response to the ineffectiveness of the social welfare service system faced by the community, even though a Community Social Worker (PSM) unit has been formed which functions as a partner of the Cirebon City Social Service (Dinsos). The research method uses a qualitative approach, namely collecting data through observation, Focus Group Discussion (FGD), and literature review. The informants in this research were PSM and Social Service officers in the field of social protection and security services. The research results show that in Cirebon City, there has not been a Social Health Center that functions as a center for information and data, providing services and an integrated referral system to the community. So PSM, whose function is to help implement social welfare services, cannot play their role effectively. This shows the urgency of establishing a Community Health Center as a forum for social welfare services at the sub-district level. Implementation of services in the Social Health Center uses an Integrated Service and Referral System, namely providing social welfare services collaboratively with the community in dealing with problems and developing existing social welfare potential. So that shared responsibility is created, not only involving the government but the private sector and society.